Decision sprint : the new way to innovate into the unknown and move from strategy to action - Rafiq, Atif (McGraw Hill-Ascent Audio, 2023)
It's no secret that steering a business has become dramatically more complex and uncertain in our modern era. Constant exploration of new territory by teams is the name of the game. Yet most companies are stuck with yesterday's approach to problem solving. Having reached the highest levels of the Fortune 500, digital disrupter Atif Rafiq has written Decision Sprint to pull the curtain back on the hidden management systems within your organization that impact how people think, collaborate, and make decisions. Talent is vital to any company's advancement, but it's the collaboration and problem solving systems that separate industry leaders from the rest. Systems designed to embrace unknowns are the quickest, most enduring way to foster growth, continuous innovation, and results. Learn how teams begin with upstream work-the phase of a promising idea or initiative where the unknowns predominate-to problem-solve anything, thus unlocking downstream actions from alignment to decision making to execution. With Rafiq's guidance, you'll overtake your competitors by moving upstream, embracing workflows that convert unknowns to clear recommendations, alignment, and action. In addition, you'll receive advice from the CEOs/presidents of H & R Block, Volvo, Peacock, and Orange Theory Fitness, among others-and learn from in-depth case studies.